Is person‐centred counselling effective when assisting young people who have experienced bullying in schools?. Issue 4 (26th March 2020) - Jones, Callum
Abstract: Background: The effects of bullying on children have profoundly been researched; however,  there is a gap in research on how therapy can assist children who are bullied. The aim of this research was to understand how person‐centred therapy may assist individuals who are being bullied within the school environment. Methodology: Person‐centred therapy was chosen as it is the author's profession. When pursuing his master's degree and the allied research programme, the author conducted the therapy. This research was performed using interpretative phenomenological analysis. The researcher worked with four research participants, and the contributors were individuals who had left school due to childhood bullying. The participants also underwent person‐centred therapy to work through the issues that bullying had caused them. A series of interviews were conducted with the participants using pre‐decided questions. These interviews were then transcribed, and key themes were found within the text. The themes, and the subordinate themes, include the following: Childhood bullying in the context of the experience of support, and the absence of support leading to trauma. Bullying as a multifaceted experience, and bullying as an emotional communication. Childhood bullying and its association to adult mental health and adult experiences of anxiety. How person‐centred counselling helped participants, and gaining support in schools. Conclusions: The article found that in the school environment a lack of emotional support added to the trauma that the victims experienced from bullying. Bullying was experienced individually, but each participant reported it being an emotional way of communicating. The bullying the participants experienced during school lead to mental health problems in adulthood, the most reported mental health condition was anxiety. Finally, the article explored how the person‐centred approach assisted participants, whilst most participants found the approach to be very useful. A few participants believed that the limitations of the person‐centred approach lead to less exploration, many wished for techniques to help them cope with their bullying experiences something that CBT might be more adequate for.